Fuzzy Stability of a Functional Equation Deriving from Quadratic and Additive Mappings - Sun Sook Jin; Yang-Hi Lee (Abstract and Applied Analysis)
We investigate a fuzzy version of stability for the functional equation f(2x+y)+f(2x−y)+2f(x)−f(x+y)−f(x−y)−2f(2x)=0 in the sense of Mirmostafaee and Moslehian.